Love & Literacy : A Practical Guide for Grades 5-12 to Finding the Magic in Literature. - Bambrick-Santoyo, Paul (Jossey-Bass A Wiley Brand, 2021)
When our students enter middle and high school, the saying goes that they stop learning to read and start reading to learn. Then why is literacy still a struggle for so many of our students? The reality is that elementary school isn’t designed to prepare students for Othello and Song of Solomon: so what do we do?